Synthesis and pharmacological evaluation of mono-arylimidamides as antileishmanial agents - Zhu, Xiaohua (Bioorg Med Chem Lett, 2016)
Arylimidamide (AIA) compounds containing two pyridylimidamide terminal groups (bis-AIAs) possess outstanding in vitro antileishmanial activity, and the frontrunner bis-AIA DB766 (2,5-bis[2-(2-isopropoxy)-4-(2-pyridylimino)aminophenyl]furan) is active in visceral leishmaniasis models when given orally. Eighteen compounds containing a single pyridylimidamide terminal group (mono-AIAs) were synthesized and evaluated for their antileishmanial potential. Six of these compounds exhibited sub-micromolar potency against both intracellular Leishmania donovani and Leishmania amazonensis amastigotes, and three of these compounds also displayed selectivity indexes of 25 or greater for the parasites compared to a J774 macrophage cell line. When given orally at a dose of 100 mg/kg/day for five days, compound 1b (N-(3-isopropoxy-4-(5-phenylfuran-2-yl)phenyl)picolinimidamide methanesulfonate) reduced liver parasitemia by 46% in L. donovani-infected mice. Mono-AIAs are thus a new class of candidate molecules for antileishmanial drug development.